The Dark Side of Modernization in The Tharu - Kandel, Churamoni (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2025)
This research paper examines and analyzes the impact of modernization on the traditional bonds that define the Tharu community in Ramesh Bahadur Chaudhary’s novel, The Tharu. Through key themes like the fragmentation of extended families, the declination of communal labour, generational conflict, the commoditization of land, and the marginalization of cultural practices, this article explores how modernization disrupts the social, economic, and cultural fabric of the Tharu people. The novel makes a study how modernization erodes the traditional values and communal structures that once sustained the community, leading to a profound loss of identity, cultural displacement, and the weakening of social cohesion. Employing a qualitative approach, the research integrates textual analysis of the novel with scholarly insights on indigenous studies, modernization theory, and cultural displacement to contextualize the novel’s representation of modernization’s effects. The study resilience. underscores how modernization, while offering economic progress and new opportunities, comes at the significant cost of cultural erosion and social fragmentation. Additionally, it sheds light on the intergenerational tensions and conflicts caused by competing worldviews of tradition and modernity. This paper explores the importance of sustainable modernization approaches that preserve indigenous traditions and cultural identities, enabling economic development without sacrificing heritage. Ultimately, the findings emphasize the need for deeper reflection on how indigenous communities like the Tharu can adapt to modernization’s forces while retaining their cultural integrity and social resilience.